Noninvasive temperature estimation in tissue via ultrasound echo- shifts. Part II. In vitro study - Sanghvi, Narendra T.; Damianou, Christakis A.; Maass-Moreno, Roberto (My University, 1996)
Time shifts in echo signals returning from a heated volume of tissue correlate well with the temperature changes. In this study the relationship between these time shifts (or delays) and the tissue temperature was investigated in excised muscle tissue (turkey breast) as a possible dosimetric method. Heat was induced by the repeated activation of a sharply focused high-intensity ultrasound beam. Pulse echoes were sent and received with a confocal diagnostic transducer during the brief periods when the high- intensity ultrasonic beam was inactive. The change in transit time between echoes collected at different temperatures was estimated using cross- correlation techniques. With spatial-peak temporal-peak intensities (I(SPTP)) of less than 950 W/cm2, the delay versus temperature relationship was fit to a linear equation with highly reproducible coefficients. The results confirmed that for spatial-peak temperature increases of ~10 °C, temperature-dependent changes in velocity were the single most important factor determining the observed delay, and a linear approximation could produce accurate temperature estimations. Nonlinear phenomena that occurred during the high-intensity irradiation had no significant effect on the measured delay. At I(SPTP) of 1115-2698 W/cm2, the delay-temperature relationship showed a similar monotonically decreasing pattern, but as the temperature peaked its slope gradually increased. This may reflect the curvilinear nature of the velocity-temperature relationship, but it may also be related to irreversible tissue modifications and to the use of the spatial-peak temperature to experimentally characterize the temperature changes. Overall, the results were consistent with theoretical predictions and encourage further experimental work to validate other aspects of the technique.
Keywords: Musculoskeletal system; Ultrasonics; Ultrasound